ANALISIS KUALITAS PELAYANAN PUBLIK (STUDI KEPUASAN PELANGGAN PADA PLN-RAYON SOE DI WILAYAH KERJA PUSKESMAS TOBU, KABUPATEN TIMOR TENGAH SELATAN) - Cahyo Sasmito; Adelvia Nabunome (Universitas Tribhuwana Tunggadewi, 2018)
The quality of public services that given low by the Limited Liability Company (PLN) on Soe Rayon as a service provider in the field of electricity for the people in South Timor Tengah District, causes public as the customers dissatisfaction.In real terms, the public dissatisfaction is caused by frequent power cuts, which can damage and by the same time disrupt the public activities. Electricity is one of the basic needs in people's daily lives, the function of electricity is used for: energy sources for electronic equipment, lighting, cooking, and as a support in providing health services and so on. The research was conducted at PLN SoeRayon for 4 months, from January to April 2016. This research used Qualitative Descriptive as the approach technique, and purposive sampling as the sampling technique. Primary and secondary data are the types of data sources, while the monitoring instrument uses interview guidelines, which are supported by observation and documentation. Data Analysis used Interactive Model Miles and Huberman, data collection through: data reduction followed by data presentation, and finally conclusions. The results of the analysis in this research indicated that: the quality of existing public services at PLN Soe Rayon was unsatisfactory, Its due to frequent occurrence of power out ages, and the slow service provided by Sub Rayon, and the transactions pay ofworse electricity. The inhibiting factor in providing services at PLN Soe Rayon is the electrical energy sources lack, thenthe natural factors that do not support, and on the other one is there’s theft on this distict, and also the lack of employees. While the supporting factors, physical facilities are sufficient, which have been given to people who are PLN's SoeRayon customers and the ability of employees who are ready to give their good service to the customers.The low quality impact of services provided by the State Electricity Company to customers in the Tobu Health Center, and generally the people of Timor Tengah Selatan Regency is the decline of customer trust to the PLN.